1994
DOI: 10.1007/bf00225139
|View full text |Cite
|
Sign up to set email alerts
|

A diallel analysis of heterosis in elite hybrid rice based on RFLPs and microsatellites

Abstract: Hybrid rice has contributed significantly to the dramatic increase of rice production in the world. Despite this, little attention has been given to studying the genetic basis of heterosis in rice. In this paper, we report a diallel analysis of heterosis using two classes of molecular markers: restriction fragment length polymorphisms, (RFLPs) and microsatellites. Eight lines, which represent a significant portion of hybrid rice germ plasm, were crossed in all possible pairs, and the F1s were evaluated for yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 28 publications
5
99
2
1
Order By: Relevance
“…For binary traits, such as those frequently used in human disease case-control studies, more complex genetic models, including dominance and overdominance, can be explicitly tested (39,40). Although this is rarely done in the analysis of continuous traits, a few studies have reported associations of heterotic traits with heterozygosity (41)(42)(43)(44)(45). We selected two linear mixed models to search for associations between genotype and phenotype using FaSTLMM software in the easyGWAS framework (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…For binary traits, such as those frequently used in human disease case-control studies, more complex genetic models, including dominance and overdominance, can be explicitly tested (39,40). Although this is rarely done in the analysis of continuous traits, a few studies have reported associations of heterotic traits with heterozygosity (41)(42)(43)(44)(45). We selected two linear mixed models to search for associations between genotype and phenotype using FaSTLMM software in the easyGWAS framework (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, despite the morphological distance detected between genotypes, it is possible that at the molecular and pedigree levels, the differences have not been properly assessed, requiring a sampling that includes genotypes with larger phenotypic differences. This hypothesis was considered in rice, for which signifi cant differences were found only between molecular (RFLP) distances and the performance of grain yield, while hybrids were established with parents of high genetic divergence, i.e., indica x japonica crosses (Zhang et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Crosses NERICA 15 × NERICA 2, NERICA 1 × NERICA 15, NERICA 11 × NERICA 15 and NERICA 2 × NERICA 15 were top ranked for one or more drought tolerant trait(s) and yield components. All these crosses had either or shared one of the good parent combiner with drought tolerance traits signifying that these crosses will eventually yield desirable transgressive segregants (Zhang et al, 1994;Li et al, 2002;Alam et al, 2004). …”
Section: Discussionmentioning
confidence: 99%